AWAL PENGISIAN WADUK PADA WADUK JRAGUNG SEMARANG - Muhammad Hafiz Adilla; Suharyanto; Dyah Ari Wulandari (LPPM Universitas Abdurrab, 2025)
The operation of a reservoir begins with a period of reservoir filling or impounding. In the process, reservoir filling will take a long time if the inflow discharge is too little, which can result in supply disruptions downstream of the dam. Meanwhile, if the inflow discharge is too large, it will fill the reservoir too quickly which can affect the completion of the remaining work and can increase the risk of dam collapse. The research aims to analyze the discharge into the reservoir and simulate and predict the duration and rate of water rise in filling the reservoir. The method used is the determination of watershed parameters with calibration and validation based on observation discharge data, followed by analysis of river flow discharge using FJ Mock. The Impounding simulation using the mainstay discharge of the FJ Mock model results in various inflow scenarios. The simulation results of the rate and duration of the most optimal reservoir water level rise to reach the Intake Gate elevation in the Wet Year is November at 0.79 m/day for 29 days. The normal Year is November at 0.68 m/day for 34 days. While in the Dry Year is December at 1.00 m/day for 23 days. Considering the safety factor, impounding should start in November because the water rise rate is quite large but does not exceed the regulations.